"There's No Thing as a Whole Story": Storytelling and the Healing of Sexual Violence Survivors among Women and Girls in Acoliland, Northern Uganda. Issue 1 (1st September 2017) - Bamidele, Oluwaseun
Abstract: Storytelling has become an important and acceptable tool among academics and professional peace‐builders. Storytelling can be therapeutic, especially since it assists survivors and the society in transition to come to terms with a traumatic past. It has been included as a part of transitional justice mechanisms which have assisted in the area of truth‐finding and accountability. It has been useful for peace‐building in communities that are deeply rooted in conflict and, therefore, has been encouraged within the last decade in a number of countries around the world. Consequently, this paper is a critical exploration of the discursive links between sexual violence and storytelling in war and peace. The focus is on Acoli women and girls in Acoliland, northern Uganda, who have primarily been impacted by the Lord's Resistance Army (LRA) group of Joseph Kony. Their stories of trauma, resilience, and courage in the face of terror have not been properly acknowledged. Using women and girls of the Acoli community in northern Uganda as an example, this paper aims to begin a discussion on the role of storytelling in the healing of sexual violence survivors. Informed by the storytelling discourse, the paper argues that constructive storytelling exercises can provide an avenue for survivors of sexual violence to acknowledge trauma, attain healing, build resilience, and counter the violent narrative of the group. However, this study also finds that storytelling as a peace‐building tool falls short of transforming gender relations. Finally, the paper proposes and designs a storytelling program.